Pedagang Kaki Lima (PKL) dan Jaringan Sosial: Suatu Analisi Sosiologi - Bukhari Bukhari (Sociology Department Of Syiah Kuala University, 2017)
This paper examines how social work takes place along with other people who like to behave similarly to the existing business people in peunayong market environment. This study uses a qualitative approach, with this approach the data produced by the descriptive of the word spoken and written, and the behavior that can be observed from the person being studied. The results of the analysis show that the network and collectivity of street vendors is a manifestation of the interdependence of fellow street vendors / marketers and it is embedded in the concept of entrepreneurship itself. The existence of an adequate and orderly network will make the poor able to create opportunities and compete to get out of poverty.Keywords: Street Vendors, Network, Collectivity